The Impact of AI Adoption on the Productivity of Tax Consultants: The Moderating Effect of Digital Literacy - Mutmainnah; Novia Ramadina (IECON: International Economics and Business Conference, 2025)
This study aims to analyze the influence of Artificial Intelligence (AI) adoption on the productivity of tax consultants, with a special focus on the role of digital literacy as a moderation variable. The approach is quantitative, with data collection through the dissemination of structured questionnaires compiled based on the General Attitudes toward Artificial Intelligence Scale (GAAIS) instrument. The questionnaire was distributed to 217 tax consultants registered as Indonesian Tax Consultants Association (IKPI) members. The results show that the adoption of AI has a significant influence on increasing the productivity of tax consultants. In addition, digital literacy has been shown to strengthen these relationships, where tax consultants with high levels of digital literacy experience greater productivity gains from using AI than those with low digital literacy. These findings confirm the importance of improving digital literacy and skills among tax professionals to optimize the benefits of AI technology. This research contributes to the literature on technology adoption in the professional services sector and offers practical implications for policymakers and professional training institutions.